Analyzing the sourcing literature: Over two decades of research. Issue 5 (December 2019) - Giunipero, Larry C.; Bittner, Samantha; Shanks, Ilana; Cho, Mee Hee
Abstract: Sourcing is an essential component of purchasing and supply chain management and has been extensively studied by academic researchers. A comprehensive scholarly literature review of sourcing was undertaken to provide guidance for future scholars through an in-depth review of past research. A total of twenty journals were selected, and 520 articles addressing sourcing topics were identified from 1995 to the present. The review process identified seven major sourcing categories within the literature. These included: strategic and relational, transactional/tactical, sourcing tools, global, sustainability, services, and new product development. Each of the seven sourcing categories is separately discussed by focusing on main themes, theories and methods. Findings indicated that strategic and transactional categories received the most attention from researchers. The area of sustainable sourcing has increased the most dramatically, while sourcing tools proved the most stable over the four time periods studied. Over 120 different theories were used to explain sourcing actions, with transaction cost economics being the most prominent. Surveys and quantitative modeling were the two most widely utilized research methods. Finally, conclusions to our findings are presented. Highlights: Sourcing research has substantially grown as a topic of interest since 2010. Sourcing research can be broadly classified into seven different categories. The most prominent category of the sourcing literature involves strategic issues. Transaction costs and a resource-based view are prominent theories in sourcing. Surveys and quantitative modeling are common methods in sourcing research.